'Localitis' in State Diplomacy: A Study on Cultural Immersion and its Effects on the Indian Foreign Service. (March 2021) - Komath, Ashwath
Literature in Diplomatic Studies often reference a phenomenon where diplomats sent for too long to another country develop an affinity for their assigned country, sometimes to the detriment of their home country. This has profound implications when we examine diplomatic agents as personalities in their own right and their ability to perform as state agents. This article investigates the basis of such a claim by examining the Indian diplomatic corps as a case study to verify its validity and enlist the factors that influence this phenomenon. This article relies on interviews given by former diplomats of the Indian Foreign Service to highlight the structures that influence behaviour of diplomatic agents and the implications it may have on training for future diplomats and preparing them for the evolution of diplomacy in the technological age.